An Inkjet Printed CO2 Gas Sensor. (2015) - Andò, B.; Baglio, S.; Di Pasquale, G.; Pollicino, A.; D'Agata, S.; Gugliuzzo, C.; C. Lombardo,; Re, G.
Abstract: In this paper a low cost CO2 sensor realized on a plastic substrate is presented. The sensor is realized by the deposition of a double layer of PEDOT/PSS (CLEVIOS™ PHCV4, by H.C. Starck) and Graphene on InterDigiTed electrodes printed onto a PET (PolyEthylene Terephthalate) substrate. The InterDigiTed electrodes have been realized by inkjet printing a conductive pattern of a silver nano-particle solution (Metalon® JS-B15P by Novacentrix), through a commercial EPSON® inkjet printer. The sensing principle of the sensor exploits the change in electrical conductivity of graphene due to gas molecules adsorbtion. A device responsivity, at 30 °C, of 45 μOhm/ppm and a sensitivity of 100 ppm have been obtained respectively. Compared to solutions proposed in the literature, the inkjet printed device here presented has advantages related to its low cost, flexibility and low demanding fabrication. The device flexibility is crucial for application requiring the device shaping to irregular surfaces, such as dresses or food packaging.